2017
DOI: 10.1039/c7ra01728f
|View full text |Cite
|
Sign up to set email alerts
|

Ag3PO4/CoFe2O4 magnetic nanocomposite: synthesis, characterization and applications in catalytic reduction of nitrophenols and sunlight-assisted photocatalytic degradation of organic dye pollutants

Abstract: ) radicals were the main reactive species for dye degradation in the present sonocatalytic system. A proposed mechanism for the enhanced photocatalytic activity is also discussed based on the experimental results. In addition, the catalytic activity of the nanocomposite in the reduction of nitrophenols by using NaBH 4 was evaluated. The results showed that Ag 3 PO 4 /CoFe 2 O 4 exhibited the best performance in the reduction of 4-nitrophenol (4-NP) and 2-nitrophenol (2-NP) and revealed 100% conversion into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 62 publications
(30 reference statements)
1
20
0
Order By: Relevance
“…The completion of the reduction was further confirmed by the appearance of new peak at 290 nm. [145] The optimization for the nitro-reduction was started firstly by choosing the best condition at which the reduction proceeds quickly. For this the reaction was tried at three different conditions such as at room temperature, under refluxing on water bath and under sonication using ml of aqueous solution of 2 N.P (0.1 mmol), 15 ml of freshly prepared aqueous solution of NaBH 4 (0.50 mol), followed by the addition of 10 mg of the catalyst.…”
Section: Catalytic Application Of Lfo Nps In the Reduction Of Nacsmentioning
confidence: 99%
“…The completion of the reduction was further confirmed by the appearance of new peak at 290 nm. [145] The optimization for the nitro-reduction was started firstly by choosing the best condition at which the reduction proceeds quickly. For this the reaction was tried at three different conditions such as at room temperature, under refluxing on water bath and under sonication using ml of aqueous solution of 2 N.P (0.1 mmol), 15 ml of freshly prepared aqueous solution of NaBH 4 (0.50 mol), followed by the addition of 10 mg of the catalyst.…”
Section: Catalytic Application Of Lfo Nps In the Reduction Of Nacsmentioning
confidence: 99%
“…To show the benet of the present degradation strategy, the obtained results from sonodegradation of RhB over the MIL-101(Cr)/CoFe 2 O 4 nanocomposite were compared with some reported catalysts in the literature. 3,18,[42][43][44][45][46][47][48][49][50] The comparison between the results in this study with the catalysts in the literature in shown in Table S1 † based on different parameters including initial dye concentration, degradation time, consumed catalyst amount and percentage, which illustrates the excellent degradation efficiency of the MIL-101(Cr)/CoFe 2 O 4 nanocomposite. Especially, the degradation reaction in the presence of most detailed catalysts took longer times and required a higher catalyst to dye ratio.…”
Section: Sonocatalytic Activity Of Mil-101(cr)/cofe 2 O 4 Nanocompositementioning
confidence: 88%
“…22-1086). 35 The existence of several diffraction bands was attributed to the POM polyanion and CFO nanoparticles in Fig. 1d and e, respectively, though with very poor intensities, indicating the homogeneous distribution of the POM polyanions and CFO nanoparticles in the mesoporous structure of Cr-MIL-101.…”
Section: Adsorption Testsmentioning
confidence: 91%
“…5b) and RhB (Fig. 6b) from aqueous solutions via POM/CFO/MIL-101(Cr) was checked at several temperatures (25,35,45,55,65, and 75 C) under xed conditions of pH ¼ 6 and adsorbent dosage of 30 mg. The increase in the adsorption efficiency with temperature indicates that the dye absorption is a spontaneous and endothermic process.…”
Section: Dye Adsorption Studymentioning
confidence: 99%